Religion and Violence in Popular Film - Stone, Bryan P. (The journal of religion and film, 1999)
Contemporary viewers of popular film are likely to have their values, perceptions, and behavior with regard to violence shaped by the cumulative effect of film conventions and recurrent images. An analysis of the top grossing films during the 1990's reveals that when religion is portrayed in connection with violence, it is rarely taken seriously as a motivating force for rejecting violence. On the contrary, while religion can play a chaplaincy or sanctuary role on screen for victims of violence, it typically serves either as a force for justifying and legitimating violence or as a device for enhancing the entertainment value of violence. In either case, we as filmgoers are steadily habituated to violence as both "natural" and "right."